The wisdom of e-crowds: Can masses create value? - Marcin Wieczerzycki (International Journal of Management and Economics, 2016)
With the rising popularity of the Internet, interactions between companies and their consumers have become more common and meaningful. Researchers often tend to apply the metaphor of community to these on-line networks of B2C relationships. However, this term implies durability and a long-term orientation. It does not cover more incidental, short-lived groups of consumers, who therefore should not be treated as communities. The purpose of this paper is to explore the ability of these short-term, collective consumer phenomena (addressed as e-crowds within the scope of this paper) to create value. Based on a critical literature analysis that considers works from several different fields of knowledge (including management, economics, psychology and media studies) and empirical examples, we argue that while lacking a complex internal organization, e-crowds are capable of creating use, exchange and sign value when certain conditions are met. However, they are equally likely to perform value-destroying activities, which present real risks for companies that interact with e-crowds.
Keywords: M31; Z13; L14; 650; crowdsourcing; value creation; crowd; e-crowd; public; consumer behavior